Uncovering "Regimes of Truth": Locating and Defining Discourses Associated with Hydro-Electric Development in New Zealand - Wells, Philippa Katherine (Auckland University of Technology, 2004)
This thesis reveals and explores a history of the New Zealand present, providing insight into myths through which New Zealanders shape their perceptions and relationships with the world that surrounds them, and interrogating the concepts that support those myths. This myth referred to is a regime of truth based on perceptions of environmental responsibility, embodied in language, policy, actions, and incorporated into official discourse through imagery, an international government-driven advertising campaign portraying a "100% Pure New Zealand" and institutionalisation. There is a Department of Conservation, a Ministry for the Environment, National Parks and Reserves and a Resource Management Act based on a fundamental principle of sustainable management. Popular discourse also recognises environmental values - hence the appearance of concerted public and media campaigns against proposed development of coastal and timbered areas and the survival of lobby and pressure groups based on environmental causes such as opposition to genetic modification and the alienation of areas considered of natural significance. However, a study of relevant strains of discourse in the New Zealand environmental context reveals ruptures and reversals, inconsistencies and contradictions. The focus and meanings within discourse have changed; the position and power of the environment has been both affected by, and has affected, power relationships. At certain times and in particular social conditions, an environmental voice has been compelled to occupy a space on the outskirts of a dominant discourse and to comply with its discursive practices, as a way of gaining legitimisation. At others, an environmental discourse has gained a fleeting triumph, to be privileged as truth. From the official outset of European colonisation in 1840, a discourse grounded in such modernist values as technological optimism, economic progress and capitalism both framed and legitimised utterances of the colonists and grounded decisions that were to fundamentally and permanently affect the New Zealand physical environment. Themes that were to echo through the years in such discursive enunciations as acclimatisation and engineering were justified on the basis of "progress". Such themes included the presumption that "man" and fulfilment of "his" needs was the ultimate dictate, and that this could and would be achieved through scientific discovery and its application through engineering and arts. Only through such a pursuit could civilisation advance onwards and upwards along a never-ending path. Within such a discourse, Nature had no distinct or valid domain outside that of man, but was merely a storehouse of raw materials, to be dipped into by Man when and where desired. One of the most significant manifestations for New Zealand in the twentieth century of this modernist discourse has been the development of hydro-electricity. The availability of the necessary technology in a country boasting plentiful rainfall, numerous fast-flowing rivers, pockets of population and a tradition of socialist, centralist political philosophy shaped hydro-electricity as a metaphor for New Zealand-style civilisation - enabled and controlled through government decision-making. Consequently, a genealogical study of the discourses relating to hydro-electricity policy and debate can provide valuable insight into the power relations between those exercising power through a modernist discourse and an environmental resistance, and into strategies that were adopted or developed as part of such discourses in the exercise of power. In particular, a detailed study of specific examples permits the interplay of socio-temporal factors and practices to be appreciated. Hydro-electricity is thus the contextual focus selected in this thesis, a focus reflected in the title. The genealogical method involves uncovering and contextualising primary and secondary materials within their historical setting. Through the interrogation of such materials this approach contributes to a critical understanding of power relations and how those relations influence strategies that might be utilised in the exercise of power. Such a method was therefore selected to analyse the tensions implicit in discourse within three historically and contextually specific case studies. These case studies involved in chronological order the proposal to harness the waters of the Bowen Falls in Fiordland during the 1920s, the proposal to raise the level of Lake Manapouri (together with that of the neighbouring Lake Te Anau) in the 1960s, and finally the proposal to divert a large proportion of the mean water-flow of the Lower Waitaki river during the first part of the twenty-first century. A principal conclusion that is reached through the analysis is that the present environmental discourse in New Zealand is not the inevitable outcome of progressive and logical history. Nor can it be explained as chance or as a consequence of world changes, but is a function of power/knowledge. Changes in the regime of truth are therefore the outcome of a successful power strategy exercised by a resistance in challenging that regime of truth. In addition, what might be defined as "environmental discourse" in the New Zealand context is narrowly defined, limited by environmental cause, a cause shaped in turn by the language of conservation. The lesson from history is that the regime of truth of such a discourse is not an end, stable and unchanging for the future, but must be seen rather as brittle, uncertain and vulnerable to attack. A third conclusion that emerges from the hydro-electricity focus is that this particular discursive enunciation of a New Zealand-style modernist discourse was a metaphor for social and economic progress, thereby occupying a privileged position as truth. Finally, one of the important contributions to methodological debate made by the thesis lies in its application of the Foucauldian genealogical method in exploring the general history of a socio-temporal context, thereby uncovering power strategies effected through discourse. This in turn reveals the hidden events, the silent voices and the games played in establishing and challenging a regime of truth.
Keywords: Hydroelectric power plants; Environmentalism; Business